High-Intensity Focused Ultrasound (HIFU) Triggers Immune Sensitization of Refractory Murine Neuroblastoma to Checkpoint Inhibitor Therapy - Eranki, Avinash; Srinivasan, Priya; Ries, Mario; Kim, AeRang; Lazarski, Christopher A; Rossi, Christopher T; Khokhlova, Tatiana D; Wilson, Emmanuel; Knoblach, Susan M; Sharma, Karun V; Wood, Bradford J; Moonen, Chrit; et al. (American Association for Cancer Research Inc., 2020)
Purpose: Immunotherapy promises unprecedented benefits to patients with cancer. However, the majority of cancer types, including high-risk neuroblastoma, remain immunologically unresponsive. High-intensity focused ultrasound (HIFU) is a noninvasive technique that can mechanically fractionate tumors, transforming immunologically ''cold'' tumors into responsive ''hot'' tumors. Experimental Design: We treated <2% of tumor volume in previously unresponsive, large, refractory murine neuroblastoma tumors with mechanical HIFU and assessed systemic immune response using flow cytometry, ELISA, and gene sequencing. In addition, we combined this treatment with aCTLA-4 and aPD-L1 to study its effect on the immune response and long-term survival. Results: Combining HIFU with aCTLA-4 and aPD-L1 significantly enhances antitumor response, improving survival from 0% to 62.5%. HIFU alone causes upregulation of splenic and lymph node NK cells and circulating IL2, IFNg, and DAMPs, whereas immune regulators like CD4 þFoxp3 þ, IL10, and VEGF-A are significantly reduced. HIFU combined with checkpoint inhibitors induced significant increases in intratumoral CD4 þ, CD8a þ, and CD8a þCD11c þ cells, CD11c þ in regional lymph nodes, and decrease in circulating IL10 compared with untreated group. We also report significant abscopal effect following unilateral treatment of mice with large, established bilateral tumors using HIFU and checkpoint inhibitors compared with tumors treated with HIFU or checkpoint inhibitors alone (61.1% survival, P < 0.0001). This combination treatment significantly also induces CD4 þCD44 þhiCD62L þlow and CD8a þCD44 þhiCD62L þlow population and is adoptively transferable, imparting immunity, slowing subsequent de novo tumor engraftment. Conclusions: Mechanical fractionation of tumors using HIFU can effectively induce immune sensitization in a previously unresponsive murine neuroblastoma model and promises a novel yet efficacious immunoadjuvant modality to overcome therapeutic resistance.
Keywords: Taverne; Oncology; Cancer Research; Journal Article